Use of Berlin Heart EXCOR extracorporeal heart systems in patients with critical heart failure - L. A. Bockeria; K. V. Shatalov (Трансплантология (Москва), 2018)
The paper describes the experience of the A.N. Bakulev Research Center of Cardiovascular Surgery, Russian Academy of Medical Sciences, in using a Berlin Heart EXCOR extracorporeal heart system (Germany) to treat critical heart failure. Artificial heart ventricles (AHV) were implanted in 8 patients who were waiting for cardiac transplantation and had a limited probability of survival and unoperated defects. The main medical and technical characteristics of the systems and the patient’s clinical status in the preoperative and immediate and late postoperative periods are presented. Indications for and contraindication to implantation of the systems and their possible application modes are considered. Equipment and a procedure for AHV implantation in different positions of afflicted heart bypass are detailed. Approaches to postoperative management and treatment policy for postoperative complications are described in detail.